Impacts of future weather and climate extremes on United States infrastructure : assessing and prioritizing adaptation actions - Tye, Mari R.; Giovannettone, Jason P. (American Society of Civil Engineers, 2021)
"This report provides prioritization frameworks in accommodating projected future weather and climate extremes for policy makers and engineers involved in infrastructure planning and design"--